127k views
2 votes
Determine the inverse of f(x)=x-2 algebraically

User Ataddeini
by
5.3k points

1 Answer

2 votes

Answer:

The answer is

f-¹(x) = x + 2

Explanation:

To find the inverse of f(x) equate f(x) to y

That's

y = f(x)

y = x - 2

Next interchange the terms.

That's x becomes y and y becomes x

We have

x = y - 2

Make y the subject

Send 2 to the left side of the equation

y = x + 2

We have the final answer as

f-¹(x) = x + 2

Hope this helps you

User Mancocapac
by
5.4k points